BUILDING INFORMATION MODELING BASED BUILDING SUSTAINABILITY ASSESSMENT FRAMEWORK FOR KAZAKHSTAN - Akhanova, Gulzhanat; Nadeem, Abid; Kim, Jong R.; Azhar, Salman; Khalfan, Malik (Buildings, 2021)
The use of building information modeling (BIM) for building sustainability assessment (BSA) is a thriving topic within the architecture, engineering, and construction industry. Despite the various research approaches to employing BSA with BIM support, the research is limited to the BIM implications of BSA methods in developing countries. This paper presents how BIM can assist the BSA processes in Kazakhstan, using a previously developed building sustainability assessment framework for Kazakhstan (KBSAF). This framework has 46 assessment indicators grouped into nine assessment categories. The categories and assessment indicators of KBSAF were derived considering the regional variations and country-specific differences in the assessment factors. In this paper, BIM functions for BSA were identified through literature review; their applicability for KBSAF was evaluated by mapping the functions with the assessment indicators of KBSAF and a BIM-based BSA framework (BIM-KBSAF) was proposed. The proposed framework was validated through a three-round Delphi survey. One of the results demonstrates that for KBSAF, BIM can assess 24 out of 46 assessment indicators. The proposed framework could serve as a systematic guide to the application of BIM for BSA. Furthermore, it can facilitate the BSA process and save considerable time and effort.
Keywords: Type of access: Open Access; building sustainability; green buildings; building information modeling; assessment indicators; Delphi method; inter-rater agreement; conceptual framework; Kazakhstan